Symptoms induced by transgenic expression of p23 from Citrus tristeza virus in phloem-associated cells of Mexican lime mimic virus infection without the aberrations accompanying constitutive expression - Soler, Nuria; Fagoaga, Carmen; Lopez, Carmelo; Moreno, Pedro; Navarro, Luis; Flores, Ricardo; Pena, Leandro (2017)
Citrus tristeza virus (CTV) is phloem restricted in natural citrus hosts. The 23-kDa protein (p23) encoded by the virus is an RNA silencing suppressor and a pathogenicity determinant. The expression of p23, or its N-terminal 157-amino-acid fragment comprising the zinc finger and flanking basic motifs, driven by the constitutive 35S promoter of cauliflower mosaic virus, induces CTV-like symptoms and other aberrations in transgenic citrus. To better define the role of p23 in CTV pathogenesis, we compared the phenotypes of Mexican lime transformed with p23-derived transgenes from the severe T36 and mild T317 CTV isolates under the control of the phloem-specific promoter from Commelina yellow mottle virus (CoYMV) or the 35S promoter. Expression of the constructs restricted to the phloem induced a phenotype resembling CTV-specific symptoms (vein clearing and necrosis, and stem pitting), but not the non-specific aberrations (such as mature leaf epinasty and yellow pinpoints, growth cessation and apical necrosis) observed when p23 was ectopically expressed. Furthermore, vein necrosis and stem pitting in Mexican lime appeared to be specifically associated with p23 from T36. Phloem-specific accumulation of the p23158-209(T36) fragment was sufficient to induce the same anomalies, indicating that the region comprising the N-terminal 157 amino acids of p23 is responsible (at least in part) for the vein clearing, stem pitting and, possibly, vein corking in this host.